Transformation of Contour Maps to Digital terrain Model (DTM) - Hanari, Kubad Zeki (Sulaimani Journal for Pure and Applied Sciences, 2000)
Digital Terrain Model(DTM) is considered to be a new method of relief representation of the Earth surface. There are many methods to obtain data required for creation a DTM. One of the methods is transformation of the existing contour maps to DTM, which consists of laying out a grid net on the contour map and measuring the coordinates of the intersection points of the contour lines with X and Y axes of the grid net. From these data, profiles are drawn along the lines then elevations of grid nodes are obtained These are the basic data required for creation of DTM in the computers. A comparison carried out between this method and photogrammertic method of data acquisition, the results were very good and encouraging. The method is simple and gives a comprehensive visualisation of the area, which can not be imagined perfectly from contour maps. DTM's will replace contour maps in the stages of desigen and execution of Civil engineering projects in very near future.